Terrorism and antisystem nature - V.D. Chernykh, S.V. Shakhov, S.I. Sulimov, I.V. Chernigovskikh, R.A. Cherenkov (Opción, 2019)
This work is devoted to the consideration of antisystem, syncretic socio-spiritual formations of destructive orientation through case study as one of the qualitative research methods. Being the subjects and the bearers of an eclectic world-view separated from reality, the adherents of anti-systems seek to reform the social reality. The authors consider the role of terrorism in the functioning of such antisystem organizations of the past as the secret society "White lotus", the sect of the Nizarits and the religious communities of voodoo. The authors point out the groups of Islamist extremists as an example of modern anti-system terrorism.